Analysis of Geometrically Consistent Schemes with Finite Range Interaction. (31st October 2017) - Li, Hongliang; Ming, Pingbing
Abstract: We analyze the geometrically consistent schemes proposed by E. Lu and Yang [6] for one-dimensional problem with finite range interaction. The existence of the reconstruction coefficients is proved, and optimal error estimate is derived under sharp stability condition. Numerical experiments are performed to confirm the theoretical results.